2019
DOI: 10.1136/jech-2019-212706
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of physical activity from midlife to old age and associations with subsequent cardiovascular disease and all-cause mortality

Abstract: IntroductionIt is well established that physical activity (PA) protects against mortality and morbidity, but how long-term patterns of PA are associated with mortality and cardiovascular disease (CVD) remains unclear.Methods3231 men recruited to the British Regional Heart Study, a prospective cohort study, reported usual PA levels at baseline in 1978–1980 (aged 40–59 years) and at 12-year, 16-year and 20-year follow ups. Twenty-year trajectories of PA, spanning from 1978/1980 to 2000, were identified using gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 48 publications
5
42
0
4
Order By: Relevance
“…Taking up the recommendations over time, was also associated with reduced CVD and CHD risk. Recently, few studies which have examined changes in physical activity, yielded the same results as ours, in middle-aged men [ 26 , 27 , 30 ]. There are also studies showing the same results in the total population, regardless of age and gender.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Taking up the recommendations over time, was also associated with reduced CVD and CHD risk. Recently, few studies which have examined changes in physical activity, yielded the same results as ours, in middle-aged men [ 26 , 27 , 30 ]. There are also studies showing the same results in the total population, regardless of age and gender.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, the majority of previous studies measured physical activity at one time point, hence failed to address the complexity and dynamic nature of this behavior [ 21 25 ]. The few studies which consider the patterns of physical activity changes over time, are mostly conducted in developed countries [ 20 , 26 30 ]. Moreover, a large number of studies on the health effects of physical activity only considered men, and data on older women is sparse [ 24 , 25 , 31 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, physical activity paradox has been de ned as high OPA intensity increase the risk of mortality for cardiovascular events in men, whereas increasing the levels of physical activity is recommended for preventing cardiovascular events [11,14] by LTPA as recommended to prevent cardiovascular disease [29].…”
Section: Resultsmentioning
confidence: 99%
“…At present, the research on PA trajectory mainly focused on CVD and physical functioning; for example, one study showed that a 20-year PA trajectory (moderately increase in PA level from middle age to old age) was associated with a decreased risk of mortality and CVD in later life, with an observed doseresponse relationship, and that maintaining even a slight PA was helpful [12]. Another study demonstrated that compared with women in the low PA groups, those in the middle and highest PA groups had more than 5% better physical functioning performance in later life [15].…”
Section: Discussionmentioning
confidence: 99%
“…As PA varies over the life course [11], assessing within-person trajectories of PA over time would better characterize the association between PA and diseases. The existing literature on PA trajectories is mainly focused on cardiovascular disease (CVD), pancreatic cancer, and physical functioning [12][13][14][15], with limited investigations of the relationship between longterm PA trajectories and incident hypertension risk, especially in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%